IMPLEMENTATION OF ENGLISH FOR SPECIFIC PURPOSES TO ADIWANA UNAGI SUITES UBUD IN INCREASING THE SERVICE QUALITY - I Kadek Agus Bisena (Journal of Language, Literature and Teaching, 2021)
Adiwana Unagi Suites is one of the most affected businesses in the hospitality sector during the Covid-19 period, but it is one of the hotels that can survive in Ubud Bali. This hotel has a very high score of 9.6 on booking.com, but throughout 2020 there were several reviews stating that the English of the hotel staff was not good. As long as the hotel is open until the end of 2020 the management has never carried out English language training to hotel staff.The implementation of the English for Specific Purposes training was carried out using an experimental research study which was carried out for six months, from January to June 2020. The implementation was carried out using youtube as a learning medium, and other online platforms such as kahoot, google form and live worksheets.The results of the implementation of the English language training carried out showed progress where during 2020 there was never a tourist review stating a lack of English, as well as an increase in English language skills as indicated by a very significant increase in post-test scores, as well as positive feedback from management.